Effectiveness of Two Ruminally Protected Methionine Sources for Lactating Dairy Cows - M. Ardalan; F. Vargas-Rodriguez; G. I. Zanton; M. Vázquez-Añón; E. Titgemeyer; B. Bradford (Kansas Agricultural Experiment Station Research Reports, 2016)
Two sources of ruminally protected methionine were tested for their ability to provide available methionine to lactating dairy cattle. Based on milk protein yield and milk protein percent, NTP-1401 (an unreleased product from Novus International, Inc., St. Charles, MO) and Smartamine (Adisseo, αretta, GA) provided similar amounts of available methionine to the cows. These two products led to different methioninerelated compounds appearing in blood plasma, suggesting that they contained different methionine precursors.
Keywords: availability; ruminally protected methionine